Attitudes toward 'Disorders of Sex Development' nomenclature among physicians, genetic counselors, and mental health clinicians. Issue 5 (October 2018) - Miller, L.; Leeth, E.A.; Johnson, E.K.; Rosoklija, I.; Chen, D.; Aufox, S.A.; Finlayson, C.
Summary: Introduction: In 2006, nomenclature referencing atypical sex development (i.e., 'intersex') was updated, and the term disorder of sex development (DSD) was formally introduced. Clinicians, patients, and parents, however, have not universally accepted the new terminology, and some continue to use different nomenclature. This inconsistency in terminology can lead to confusion among clinicians and patients, affect clinician–patient relationships, and interfere with the recommended multidisciplinary model for DSD care. Objective: This study sought to (1) evaluate frequency of use and comfort with specific DSD terminology, (2) assess why clinicians are not using specific terms, and (3) determine what terms are being heard within the medical community and by the public in a sample of physicians, genetic counselors, and licensed mental health clinicians. Study design: A Web-based survey assessing the use of DSD terminology was distributed to endocrinologists, urologists, genetic counselors, and mental health clinicians. The survey assessed frequency of use and comfort with specific terms, negative experiences related to specific nomenclature use, and the context in which terms are used (e.g. case conference, literature, patient/parents, and media). A qualitative analysis of open-ended responses was conducted to characterize reasons for avoiding specific terms. Results: The survey was completed by 286 clinicians. There were significant differences between specialties in comfort and frequency of use of specific terms, and significant differences were based on clinician gender, patient volume, length of time in practice, and practice setting. The study results also showed a difference in the nomenclature used within the medical community versus the media. Discussion: Study findings are consistent with previous research exploring medical professionals' use of the new term: disorder of sex development . However, there continues to be inconsistency in the uptake of this new terminology. Words that have been purposed in the literature to replace disorder, such as difference and variation, would be accepted by clinicians, and the word divergent would not. This study expands on the existing literature documenting high uptake of disorder of sex development nomenclature among medical professionals. In addition, this study demonstrates that the most common diagnostic terms used by the medical community are not the same terms being presented to the public by the media. Conclusion: Medical professionals have varying preferences for terminology use when describing DSD, which can affect patient care. These results can be used in the future to compare with what patients and advocates prefer to develop a more universally accepted approach to nomenclature. Extended Summary Table   Most comfortable Most often Atypical genitalia Genital difference (82.1%) Ambiguous genitalia (40.7%) Genital structures Clitoris (96.8%); penis (97.5%); phallus (89.2%) Clitoris (76.5%); penis (78.6%); phallus (57.9%) Non-typical Variation (90%), Difference (60.4%) DSD diagnosis Disorder of sex development (86.1%) Disorder of sex development (60.9%)   Least comfortable Least often Atypical genitalia Neutral genitalia (29.6%) Neutral genitalia (1.4%); non-specific genitalia (1.4%) Genital structures Clitorophallus (53.1%); sensitive tissue (61.7%) Clitorophallus (11.1%); sensitive tissue (19.2%) Non-typical Divergent (40.1%), Divergent (3.9%) DSD diagnosis Sex development atypia (29.0%). Sex development atypia (1.4%)